Analisis Upaya Optimalisasi Relationship Management, Lokasi, dan Distribusi untuk Keberlanjutan UMKM Manika di Kalimantan Timur - maulandini, rahma a.o (BALQIS : Journal of Business Innovation and Digital Marketing, 2025)
This study investigates the influence of relationshop management, business location, and distribution optimization on the sustainability of Manikka Kaltim, a craft-based MSME in East Kalimantan. The research addresses challenges faced by local creative MSMEs, including limited resources, dependence on single suppliers and low market visibility. A qualitative descriptive approach was employed using Porter’s Five Forces Analysis, with data collected through interviews, observations, and documentation. The findings show that Manikka Kaltim operates in a highly competitive environment marked by strong buyer bargaining power, limited supplier options, and growing substitute threats. Sustainable supplier and customer relationships, supported by digital distribution strategies, were found to enhance competitiveness, while strategic location selection and integrated online-offloine marketing expanded market reach. The study concludes that the sustainability of Manikka Kaltim depends on the synergy between relationship management, startegic location, and adaptive distribution system.